In situ Raman investigation of the phase transition of NaVO2F2 under variable temperature conditions. Issue 38 (5th July 2021) - Zhang, Sa; Li, Yan; Huang, Liuqing; Huang, Liuying; Luo, Xuetao
Abstract : In this study, the phase transition of NaVO2 F2 was measured at different temperatures via in situ Raman spectroscopy. Abstract : In this study, the phase transition of NaVO2 F2 was measured at different temperatures via in situ Raman spectroscopy. The NaVO2 F2 compounds were synthesized by a hydrothermal method and were identified to be monoclinic with the P 21 / c space group at room temperature by XRD. Accordingly, the variations of Raman shifts and intensities of the characteristic peaks for NaVO2 F2 associated with temperature were obtained and investigated. It was confirmed that NaVO2 F2 had three types of phase transitions, which occurred in the temperature region from 78 K to 573 K. Further, the results indicate that transition from a low-temperature phase (I) to another low-temperature phase (II), low-temperature phase (II) to P 21 / c phase and P 21 / c phase to P 21 / m phase occurred near the three temperature points of 93 K, 233 K, and 453 K, respectively, during the heating process. Therefore, a novel characterization method was provided for further research on the phase transition theory and performance of vanadate compounds.